Quality of Prenatal Care Among Mothers in Selected Barangays in Davao City, Philippines - Kulintang, Mohammed Bien; Matutino, Regel Ivan Kent; Salas, Christian Joy; Pechera, Joyce; Mantilla, Audrey Anne; Mozar, Eranah Kaye; Mission, Gwynneth; Moro, Jasnaera (Journal of Interdisciplinary Perspectives, 2024)
Prenatal care encompasses medical attention provided to pregnant women from conception to childbirth. This study aimed to determine the association between the respondents' sociodemographic profiles and the quality of prenatal care. A descriptive, correlational research method was used in this study. Utilizing the "a priori power analysis," 120 respondents were randomly selected using the following criteria: mothers who had prenatal checkups in selected barangay health centers in a District in Davao City, of legal age, and were willing to participate in the study, after giving birth one to three months. Data were collected from March to April 2024. Results revealed that most respondents were young adult, primigravida, multiparous, with full-term babies, high school graduates, and family monthly income of 7,000 – 10,000. The quality of prenatal care was high, particularly the "information sharing," anticipatory guidance, sufficient time, approachability, availability, and support and respect. Furthermore, educational attainment, particularly undergraduates, high school graduates, and baccalaureate degree holders, and with term babies, was noted to have a statistically significant association with their quality of prenatal care. Hence, having a good educational attainment and a "term baby" reciprocates good prenatal care among the respondents. The quality of prenatal care upholds standards of giving good services and approaches that participants experience during their prenatal checkups.